Analysis of Perceived Value as an Intervening Variable of Aspect-Based Sentiment and Tourist Experience on Lake Toba Tourism Destination Development Problems - Amanda, Sharina; Astuti, Yuniar Anti; Purjianto, Purjianto (CV. Rayyan Dwi Bharata, 2024)
Tourism problems must be resolved quickly because every problem that exists will make the name of the tourist spot a negative value in the eyes of other tourists who want to visit, the tours visited at least provide comfort for visitors so that this positive value will have an impact on the decision to revisit or spread positive information to potential new tourists in the tourist environment itself. This research approach is quantitative with the Structural Equation Modeling (SEM) model. This approach is able to test the most ideal model in estimating endogenous variables. This research was conducted in the North Sumatra region, precisely at the Lake Toba tourist location and the research target was Lake Toba tourism visitors who came from outside the Tobasa Regency area, the population of Lake Toba tourists who had visited at least 250 people twice, the analysis model used to test the hypothesis in this study was multiple regression analysis using the Smart PLS application. Directly Perceived Value, Aspect-Based Sentiment and Tourist Experience have a Significant Effect on the Problems of Lake Toba Tourism Destination Development, Directly Aspect-Based Sentiment and Tourist Experience have a Significant Effect on Perceived Value of Lake Toba Tourism, Indirectly Aspect-Based Sentiment and Tourist Experience have a Significant Effect on the Problems of Lake Toba Tourism Destination Development through Perceived Value.